2011
DOI: 10.1007/978-3-642-25453-6_38
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Survey of IT Governance in Thai Universities through IT Executive Perspectives

Abstract: Abstract. IT Governance (ITG) has increasingly become an important role of university governance. Recent research has focused on the finding of effective approaches for improving ITG in the university. Similar to the focal point of Thai universities, IT executives need the progressive direction for ITG. Consequently, the objective of this research is to explore the various aspects of ITG in Thai universities by surveying. The questionnaires were distributed to 117 IT executives from 117 universities and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
1
0
6
Order By: Relevance
“…[16] investigated the issues related to IT governance in a public university in Malaysia using a case study method and found that the university lacks a common approach in decisions related to IT planning, IT funding and IT project development. [17] studied eight Australia universities and found that decentralized structure is the most common and these universities are at different levels of maturity in terms of IT [18] found IT governance at Thai universities were in the initial stage and most IT executives were not familiar with IT principles. More recently, [19] examined the role of IT executives in higher education by looking at the skills and experience necessary to be a Chief Information Officer (CIO).…”
Section: It Governance In Higher Educationmentioning
confidence: 99%
“…[16] investigated the issues related to IT governance in a public university in Malaysia using a case study method and found that the university lacks a common approach in decisions related to IT planning, IT funding and IT project development. [17] studied eight Australia universities and found that decentralized structure is the most common and these universities are at different levels of maturity in terms of IT [18] found IT governance at Thai universities were in the initial stage and most IT executives were not familiar with IT principles. More recently, [19] examined the role of IT executives in higher education by looking at the skills and experience necessary to be a Chief Information Officer (CIO).…”
Section: It Governance In Higher Educationmentioning
confidence: 99%
“…Hales, 2011); (van Wessel et al, 2011);; (Luftman et al, 1999); (Küller, Vogt, Hertweck, & Grabowski, 2012); (Jairak & Praneetpolgrang, 2011); (Bhattacharjya & Chang, 2009). Kompleksnost Stopnja, do katere je težko razumeti in uporabiti model UI.…”
Section: +200%unclassified
“…Hales, 2011); (van Wessel et al, 2011);; (Luftman et al, 1999); (Küller, Vogt, Hertweck, & Grabowski, 2012); (Jairak & Praneetpolgrang, 2011); (Bhattacharjya & Chang, 2009). Kompleksnost Stopnja, do katere je težko razumeti in uporabiti model UI.…”
Section: +200%unclassified